Food preservation under pressure (hyperbaric storage) as a possible improvement/alternative to refrigeration - Fernandes, P.A.R. (2022)
Food preservation is highly dependent on refrigeration, which is limited by its high energy costs. Among alternatives being developed, this review focused on hyperbaric storage (food preservation under pressure). This new preservation methodology has as main objective microbial growth inhibition similarly to freezing and refrigeration, showing a great potential to lower energy costs since refrigerated/room temperatures (RT) can be used. This, even at variable (uncontrolled) RT (up to 37 C), has been shown to preserve foods and thus achieving significant energy savings. Covering the earliest up to the more recent studies, this review aimed to gather information about the state of art of hyperbaric storage at refrigerated and RTs, with the primary objective of showing it potential and possible future applications of this new preservation method based on microbial growth inhibition under pressure, using pressure as the main variable to slow down microbial growth.